(untitled) (Journal of Science and Technology, 2016)
Some aspects of the breeding biology of the Blue-billed Weaver Spermophaga haematina were examined for two consecutive years (i.e. 1999 and 2000). On the commercial farm of Obafemi Awolowo University, Ile-Ife, Nigeria. Forty four visits of 128.6 man hours were utilized searching for nests. Forty one active nests were monitored daily from 07.00 to 09.00h and from 17.00 to 19.00h to record the fate of clutches. The clutch size, breeding and nesting successes, and recruitment of fledgling per breeding seasons were determined. They were found to construct loose globular nests with side entrance out of grass inflorescences. Apart from grass inflorescences some narrow grass leaves, large soft skeletonized leaves or other fine inflorescences lining the interior form part of the nests. The nests had an external mean diameter of 112.42 ± 5.07mm, mean internal diameter 71.50±5.56mm and a mean entrance diameter of 27.83±2.41mm. Blue-billed Weaver displayed a seven-month breeding season from March to September with a peak lying between April and July. The long breeding period showed the efficiency with which the species may have utilized different food resources and hence occupy broad feeding niches. The clutch size was between 1 to 3 eggs with more than 80% of the forty-one completed clutches for the two seasons accounting for 3 eggs each. The mean clutch size was 2.74 and 2.67 eggs for 1999 and 2000 respectively. Synchronous hatching of the eggs yielded nestlings of almost the same age. Adaptations to low level nesting in Blue-billed Weaver were reduced incubation period (14.00±1.21 and 15.00± 61 days for 1999 and 2000 respectively), reduced fledgling period (15.00±0.82 and 15.00±0.25 days for 1999 and 2000 respectively) coupled with rapid growth rate of the chicks which ensured survival and early departure from the nest. Recruitment was estimated at about 34 and 27 chicks for 1999 and 2000 respectively with low mortality at hatching.